Efektivitas Program Rehabilitasi Pasca Tuberkulosis terhadap Kapasitas Fungsional: Meta-Analisis - Haris Sutopo; Andreany Kusumowardani; Endang Sri Wahyuni (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Post-Tuberculosis Lung Disease (PTLD) is a common long-term consequence of pulmonary tuberculosis that may persist despite successful anti-tuberculosis treatment, resulting in reduced functional capacity. Post-tuberculosis rehabilitation has been recommended to improve physical function; however, evidence regarding its effectiveness remains inconsistent. Objectives: This study aimed to evaluate the effectiveness of post-tuberculosis rehabilitation on functional capacity through a systematic review and meta-analysis. Methods: A systematic review and meta-analysis were conducted according to the PRISMA 2020 guidelines. Literature searches were performed in PubMed, Google Scholar, and Web of Science up to 2025. Randomized controlled trials and prospective controlled intervention studies reporting Six-Minute Walk Test (6MWT) outcomes in patients with PTLD were included. Data were analyzed using Review Manager (RevMan) 5.4 with a random-effects model, and pooled effects were expressed as Mean Difference (MD) with 95% confidence intervals (CI). Results: Six studies involving 492 participants met the inclusion criteria. Post-tuberculosis rehabilitation significantly improved functional capacity compared with standard care (MD = 109.32 m; 95% CI = 44.13–174.50; p = 0.001). Despite substantial heterogeneity (I² = 98%), sensitivity analysis confirmed the robustness of the findings. Conclusion: Post tuberculosis rehabilitation effectively improves functional capacity in patients with PTLD and should be considered an integral component of comprehensive post-tuberculosis care. Keywords: Tuberculosis, Post-Tuberculosis Lung Disease, Pulmonary Rehabilitation, Functional Capacity, Six-Minute Walk Test, Meta-Analysis.